Pathogenicity of Metarhizium anisopliae and Beauveria bassiana on whitefly (Bemisia tabaci) - García Ramírez Emilio; Pérez Pacheco Rafael; León Enríquez Bernardino Leonardo; Pliego Marín Lina (Revista Mexicana de Ciencias Agrícolas, 2018)
The alternatives for the control of Bemisia tabaci are insufficient. The use of entomopathogenic fungus is one of these alternatives, but lack information regarding pathogenicity of conidia concentration and storage. Furthermore, protocols for assessing mortality have flaws that must be corrected. The research was done at the Technological Institute of Oaxaca Valley, in 2010. It were assessed two entomopathogenic fungus (Metarhizium anisopliae and Beauveria bassiana) with different concentrations of conidia for controlling B. tabaci in Solanum lycopersicum under greenhouse, using the protocol from Ortega et al. (1998) modified in this research; mortality of B. tabaci decreased by reducing the time of fasting and adapting a lace and fabric in the micropipette. For its part, the mortality of B. tabaci at all concentrations of conidia of the two entomopathogenic fungus without storage was the same as the chemical insecticide. When conidia were stored in a refrigerator, mortality was higher with treatment B. bassiana with a concentration of 2.1 x 106 conidia mL-1 and the chemical insecticide, which indicates that storage of conidia decreases pathogenicity mainly in Metarhizium anisopliae.